2017
DOI: 10.1007/s00508-017-1240-9
|View full text |Cite
|
Sign up to set email alerts
|

Citicoline in severe traumatic brain injury: indications for improved outcome

Abstract: Goal-oriented management of traumatic brain injury (TBI) can save the lives and/or improve the long-term outcome of millions of affected patients worldwide. Additionally, enhancing quality of life will save enormous socio-economic costs; however, promising TBI treatment strategies with neuroprotective agents, such as citicoline (CDP-choline), lacked evidence or produced contradictory results in clinical trials. During a prehospital TBI project to optimize early TBI care within 14 Austrian trauma centers, data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
0
5
0
1
Order By: Relevance
“…In the study by Trimmel et al [ 59 ], 67 patients with brain trauma were administered citicoline during their stay in the intensive care unit (ICU). The Rotterdam CT score, Glasgow Coma Scale (GCS), and the Injury Severity Score (ISS) were used to initially assess the condition of patients after trauma.…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Trimmel et al [ 59 ], 67 patients with brain trauma were administered citicoline during their stay in the intensive care unit (ICU). The Rotterdam CT score, Glasgow Coma Scale (GCS), and the Injury Severity Score (ISS) were used to initially assess the condition of patients after trauma.…”
Section: Resultsmentioning
confidence: 99%
“…Citicoline has a neuroprotective effect through the preservation of neuronal sphingomyelin, cardiolipin, and arachidonic content, as well as phosphatidylethanolamine and phosphatidylcholine. Citicoline also improves glutathione reductase activity and choline availability for acetylcholine synthesis (Trimmel et al, 2018). Moreover, citicoline prevents phospholipase A2 stimulation during ischemic stroke; thus, it attenuates free radical generations from cardiolipin catabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In a study investigating the effect of citicoline on patients with brain trauma, it was found that GCS in patients on the 15th day of hospitalization treated with 500mg of citicoline every 6 hours compared to the first day of hospitalization, it was associated with an increase in the degree of GCS (19). In another study investigating the patients with brain trauma with a GCS of < 13 using a 6-month follow-up, citicoline administration was reported to cause a marked decrease in mortality rate among people admitted to the ICUs (20). In an investigation including 1,213 patients with brain trauma between 2007 and 2011, no changes were observed in the GCS level in the intervention and control groups after 90 days of treatment with citicoline (two g per day) (21).…”
Section: Discussionmentioning
confidence: 99%